Scale-up of electrokinetic process for dredged sediments remediation. (20th August 2020) - Benamar, A.; Ammami, M.T.; Song, Y.; Portet-Koltalo, F.
Abstract: Most of electrokinetic remediation (EKR) reported researchs were performed on small-scale laboratory devices and less field-scale studies are available in literature. Understanding the scaling-up process is essential for the application of the EKR at field scale. This paper presents the results of laboratory experiments performed at two scales (involving 0.4 kg and 40 kg of dredged sediment) to evaluate the potential of EKR process on both organic and inorganic contaminants, and the scaling-up effect. Mixtures of eco-friendly enhancing additives were used: a biodegradable chelating agent (citric acid) combined with a nonionic surfactant (Tween 20) were promising candidates for the simultaneous EK remediation of a multi-contaminated harbor sediment. The values of energy consumption from the large scale tests showed that efficient decrease of pollutant concentrations and sustainable remediation could be achieved with moderate energy costs. Obtained results also indicated that better removals of Cr, PAHs and PCBs were achieved with the large-scale device using less energy and additives. However, the distribution of the pollutants in the specimen after the EK remediation indicated that the electric field did not totally control the migration process and that the interaction with likely heterogeneity and inertial effects reduced the EK effectiveness at the large scale. This scaling-up investigation allows considering EK tests at a larger scale (field installation) with adjusted parameters from a small-scale investigation.